PEMBERDAYAAN MASYARAKAT MUARA BELITI BARU MELALUI BUDIDAYA TANAMAN CABAI RAWIT SEBAGAI PEMANFAATAN PEKARANGAN RUMAH: Empowering The Community Of Muara Beliti Baru Through The Cultivation Of Cayenne Pepper Plants As A Home Yard Utilisation - Novianto Novianto; Renaldo Renaldo (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community empowerment of yard land is an effort made to increase the ability to utilise land resources to build the welfare of the community itself.  The problem faced by the Muara Beliti Baru Village government is that many people have not made optimal use of yard land in supporting their own household food security, so one of the efforts in the community service programme, the service team prepared an innovation package for growing cayenne pepper on yard land in supporting horticultural food needs and increasing the knowledge, skills and welfare of the village community. This community service activity uses survey, observation, interview, training, discussion and demonstration methods, taking several samples of local residents, namely PKK mothers. The results of this service activity in Muara Beliti Baru Village received a positive response from the PKK mothers in following a series of stages that had been arranged by the service team to change the mindset of the participants to have better knowledge and skills than before, almost the overall average of PKK mothers was enthusiastic, participatory and gave positive responses to carry out activities to utilise home yard land in a sustainable manner.